Analysis of the Effect of Employee Costs on Company Performance - Željko Požega; Boris Crnković (Ekonomski Vjesnik, 2010)
The goal of every economic entity is to accomplish an optimal system of compensation management and to reach maximum returns through optimal employee investment, raising their motivation and knowledge as well as developing their abilities and skills. In order to reach this goal of maximizing company performance it is necessary to systematically approach the management of human resources within a certain economic entity and to create the fairest material and non-material reward and punishment system by using compensation management methods. This in turn will bring about a positive working atmosphere in the company, where employees will rapidly and easily adjust to changes, interact and co-operate with one another at a high level. This research, which studies the effect of employee costs on company performance, is divided into three chapters. The first chapter provides a brief theoretical overview of the importance of compensation management in human resources administration and reaching business efficiency, i.e. the different possibilities of creating a reward and punishment system in a company which aims to organise an optimal working atmosphere. The second chapter demonstrates the applied methodology and illustrates the information from different companies, which has been used in this research and analysis. The information comprises statistical data of employee costs, income, profits and losses from a sample of companies from the Republic of Croatia in 2008. The third part deals with the analysis and interpretation of the research results which show the effect of employee costs on the income and company performance, also expressed per employee. The goal of this research is to test the hypothesis that companies with higher employee cost, i.e. with higher investment in human resources, on average obtain a higher income and a higher profit per employee and are more efficient and more successful on the market. From the given hypothesis, one can derive the hypothesis that compensation management in human resources administration is of crucial importance for the management of an economic entity and that strategic planning of investment and expenditure per employee is a prerequisite for the competitiveness of a business, its development and survival in an increasingly demanding market race.